CASE STUDY UNDER THE CORRELATION OF STUDENTS’ RESPOND ANXIETY TO THE LEARNING MOTIVATION AS THE IMPACT OF MODERNIZATION MEDIA USED (WHATSAPP) - Wariyati; Sujarwo; Maya Aulia (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2020)
Modernization and technology as supporters and solutions in a variety of learning problems, namely limited time to face to face, low self-confidence, limited introverted character, and lack of time flexibility to understand the material in the context of open discussion. The what’sApp application is a solution to existing problems by providing unlimited learning space and without just having to carry out discussions face-to-face. This study aims to bridge the students who have problems with the ability to respond spontaneously to learning material. This media is proven to be able to make the activity of students participating in lectures increase significantly. Learning discussions are made in a WhatsApp group by combining several classes so that there arises competitive learning interest where teaching material is shared with the presenter and respondent groups. The response given in online media using WhatsApp supports the activeness and optimism of learning. This research is a quantitative study by testing hypotheses or solving problems on the basis of theoretical deduction, by measurement using statistical data. This type of quantitative research used is a quantitative associative causal relationship, which is conducted to determine the causal relationship between the independent variable (the variable that affects) and the dependent variable (the variable that is affected). Based on the data collected, it was found that the use of WhatsApp online application media had a significant impact on increasing student motivation in participating in the learning process. This is supported by the percentage reaching 70% of students feeling so excited and freer to use the application with more motivated to be more active in lectures. Based on the results of the research questionnaire also supports that students with a high level of concern for responding to face-to-face classes become very active and helped when conducting discussions via online using the WhatsApp Application.